DETERMINANTS OF AUDITOR PERFORMANCE ON PSYCHOLOGICAL WELL-BEING ASPECTS AS A MODERATING VARIABLE (EMPIRICAL STUDY AT PUBLIC ACCOUNTING FIRMS IN NORTH SUMATRA) - Hidayatna Putri; Kusnadi (Mount Hope Economic Global Journal, 2024)
The aim of this research is to determine the influence of role of conflict and role of ambiguity on auditor performance, moderated by aspects of psychological well-being. This research used 60 samples from public accounting firms in North Sumatra. Analysis using Warp PLS 5.0. The results of the research show that when an auditor experiences role conflict it can affect the auditor's self-perception of what he does, which can affect the auditor's performance. Role ambiguity affects the auditor's performance because the auditor does not have clear objectives for his work due to the lack of clear information and direction, as well as the unavailability of a monitoring or evaluation system which can basically guide the auditor to be able to carry out his work with quality at a certain level. The psychological well-being aspect is proven to moderate the role of conflict and role of ambiguity on auditor performance.